2022
DOI: 10.1093/rheumatology/keac068
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of baricitinib and tofacitinib compared with bDMARDs in RA: results from a cohort study using nationwide Swedish register data

Abstract: Objectives To describe the use of baricitinib and tofacitinib by Swedish rheumatoid arthritis (RA) patients and to compare their effectiveness with that of biological disease-modifying anti-rheumatic drugs (bDMARDs). Methods RA patients who initiated baricitinib [N = 1420], tofacitinib [N = 316], abatacept [N = 1050], interleukin-6 inhibitors (IL6i) [N = 849], rituximab [N = 1101] or tumour necrosis factor inhibitors (TNFi) [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…Our real-world prospective analysis shows a similar time course of disease activity using DAS28 ESR under BARI-mono and BARI-combo therapy with the BARI-combo group being numerically, but not statistically better throughout almost all time points, confirming data from a randomised controlled trial and Swedish Registry data, the latter comparing BARI mono with BARI combination with csDMARDs 5 14. Furthermore, we detected similar rates of drug survival between BARI-mono and BARI-combo which is of interest for patients who do not tolerate MTX.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our real-world prospective analysis shows a similar time course of disease activity using DAS28 ESR under BARI-mono and BARI-combo therapy with the BARI-combo group being numerically, but not statistically better throughout almost all time points, confirming data from a randomised controlled trial and Swedish Registry data, the latter comparing BARI mono with BARI combination with csDMARDs 5 14. Furthermore, we detected similar rates of drug survival between BARI-mono and BARI-combo which is of interest for patients who do not tolerate MTX.…”
Section: Discussionsupporting
confidence: 80%
“…Italian and Spanish multi-centre observational cohorts confirmed the efficacy and safety profile of BARI in bDMARD-naïve RA patients and revealed that drug survival is better in patients with seropositive RA 12 13. Analysis from a Swedish registry data revealed that BARI was equally effective compared with other bDMARDs and that BARI was more commonly used as monotherapy compared with rituximab and TNFi 14. These studies have analysed the efficacy of BARI mono versus BARI combination with overall csDMARDs but detailed observational data comparing BARI monotherapy to an explicit combination with MTX with respect to treatment response and drug survival were not reported.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The difference to the general population rate was also pronounced for infections, with more than doubled rate for on February 58 (14) 58 (14) 58 (14) 56 (15) 57 ( 14) 61 ( 13) 64 ( 13) 59 ( 14) 59 ( 14)…”
Section: Incidence Rate By B/tsdmardmentioning
confidence: 99%